2016
DOI: 10.1097/iae.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious Vitritis After Intravitreal Injection of Anti-Vegf Agents

Abstract: The results suggest a difference in rates of noninfectious vitritis for antivascular endothelial growth factor medications. Many cases tended to cluster instead of occurring at a consistent rate each year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 16 publications
2
29
1
1
Order By: Relevance
“…Sterile endophthalmitis is a well-described phenomenon and is even thought to be more common with intravitreal bevacizumab over other intravitreal anti-VEGF agents. 16 However, most would agree if there is any suspicion of infection in a case of "sterile" endophthalmitis, then infectious endophthalmitis treatment should be initiated, as the visual prognosis without treatment is grim at best. After the diagnosis of endophthalmitis was made, patients received treatment on average less than 4 hours after admission to hospital, with a range of 15 minutes to 11 hours.…”
Section: Greenlane Clinical Centre Outpatient Intravitreal Injection mentioning
confidence: 99%
“…Sterile endophthalmitis is a well-described phenomenon and is even thought to be more common with intravitreal bevacizumab over other intravitreal anti-VEGF agents. 16 However, most would agree if there is any suspicion of infection in a case of "sterile" endophthalmitis, then infectious endophthalmitis treatment should be initiated, as the visual prognosis without treatment is grim at best. After the diagnosis of endophthalmitis was made, patients received treatment on average less than 4 hours after admission to hospital, with a range of 15 minutes to 11 hours.…”
Section: Greenlane Clinical Centre Outpatient Intravitreal Injection mentioning
confidence: 99%
“…Noninfectious in ammation was reported after anti-VEGF injections 37 . Although the incidence was very low, most anti-VEGF agents have caused in ammation after intravitreal injections [38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Data from a retrospective case series of injections given from 2006 to 2013 indicate the rate of noninfectious vitritis in nearly 100,000 intravitreal injections ranged from 0.02% to 0.16% for the various anti-VEGF agents. (27) For culture positive endophthalmitis in a case series of nearly 500,000 intravitreal injections in 5 retina clinics, the rates ranged from 0.035% to 0.039% for all the anti-VEGF and steroidal formulations administered. (28) Another center found that intravitreal injections of steroid resulted in 6.9 fold increased rate of endophthalmitis when compared with intravitreal injections of anti-VEGF therapies (0.13% vs.…”
Section: Discussionmentioning
confidence: 99%